Positive electrode active material, positive electrode containing the same, and lithium secondary battery

By controlling the orientation of the long axis and c-axis directions of the grains in the external region of the positive electrode active material, the unstable capacitance characteristics and gas generation problems shown by the existing positive electrode active material in battery applications are solved, and the effects of high capacitance characteristics and low gas generation are achieved.

JP7648291B2Active Publication Date: 2025-03-18LG CHEM LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023551244
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-22
Filing Date
2022-03-22
Publication Date
2025-03-18
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

There are problems with inconsistent structural and physical properties of existing cathode active materials, resulting in unstable capacitance characteristics and high gas generation in battery applications.

Method used

By controlling the orientation of the long axis and c-axis direction of the grains in the outer region of the positive electrode active material, ensure that the orientation of the long axis is between 0.5 and 1, the orientation of the c-axis is below 0.5, and the proportion in the outer region is 25% to 80%, to optimize the grain structure.

Benefits of technology

The high capacitance characteristics and low gas generation of the positive electrode active material are achieved, and the overall performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648291000011
    Figure 0007648291000011
  • Figure 0007648291000012
    Figure 0007648291000012
  • Figure 0007648291000013
    Figure 0007648291000013
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material that contains 25% to 80% crystal grains C in an outer region thereof, the crystal grains having a high degree of long axis orientation (DoA) and a low degree of c-axis orientation, and that has high capacity characteristics and low gas generation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0036942, filed on March 22, 2021, and all contents disclosed in the Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a positive electrode active material, a positive electrode and a lithium secondary battery including the same, and more particularly to a positive electrode active material for a lithium secondary battery having excellent capacity characteristics and little gas generation, and a positive electrode and a lithium secondary battery including the same. [Background technology]

[0003] Recently, with the increasing technological development and demand for mobile devices and electric vehicles, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] As the positive electrode active material for lithium secondary batteries, lithium transition metal oxides such as lithium cobalt oxides such as LiCoO2, lithium nickel oxides such as LiNiO2, lithium manganese oxides such as LiMnO2 or LiMn2O4, and lithium iron phosphate oxides such as LiFePO4 have been developed. a Co b Mn c ]O2, Li[Ni a Co b Al c ]O2, Li[Ni a Co b Mn c Al d Lithium composite transition metal oxides containing two or more transition metals, such as ]O2, have been developed and are widely used.

[0005] Lithium composite transition metal oxides containing two or more transition metals that have been developed to date are usually manufactured in the form of spherical secondary particles formed by agglomeration of tens to hundreds of primary particles, but physical properties such as lithium ion mobility and electrolyte impregnation ability vary depending on the orientation form and shape (aspect ratio) of the primary particles. Therefore, research is being conducted to improve the performance of positive electrode active materials by controlling the particle structure of the positive electrode active material particles.

[0006] Korean Patent No. 10-1611784 (Patent Document 1) discloses a positive electrode active material in which the length of the a-axis direction of the primary particles is longer than the length of the c-axis direction, and the a-axes of the primary particles are radially arranged. In Patent Document 1, the morphology and orientation of the primary particles of the positive electrode active material are analyzed using a scanning electron microscope (SEM) and / or a transmission electron microscope (TEM).

[0007] However, the TEM analysis used in Patent Document 1 has the problem that it is difficult to represent the characteristics of the entire positive electrode active material particle because it can only obtain information about a partial region, not the entire particle. In addition, since the physical properties of the positive electrode active material vary depending on not only the morphology and orientation of the primary particles, but also the morphology and orientation of the crystallines, even if the morphology and orientation of the primary particles are similar, they may show different physical properties.

[0008] Therefore, in order to develop a positive electrode active material having better properties, research into the crystal grain structure of the positive electrode active material is required. Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention is intended to solve the above-mentioned problems, and aims to provide a positive electrode active material having excellent capacity characteristics and little gas generation by containing a specific ratio of crystal grains in the outer region of the positive electrode active material particles, the orientation of the long axis and c axis of the crystal grains satisfying specific conditions.

[0010] The present invention also provides a positive electrode and a lithium secondary battery containing the positive electrode active material according to the present invention. [Means for solving the problem]

[0011] According to an embodiment, the present invention provides a cathode active material including an inner region that is a region from the center of a cathode active material particle to R / 2, where R is a distance from the center to a surface of the cathode active material particle, and an outer region that is a region from R / 2 to the surface of the cathode active material particle, wherein the degree of long axis orientation DoA of all crystal grains in the outer region, represented by the following [Equation 1], is 0.5 to 1, and the ratio C1 of crystal grains C having a degree of c-axis orientation of the crystal grains, represented by the cross product value of the c-axis rotation vector Rc of the crystal lattice of the crystal grains and the position unit vector P' of the crystal grains obtained through an electron backscatter diffraction (EBSD) analysis, is less than 0.5, is 25% to 80%, preferably 30% to 60%, more preferably 30% to 50%, and even more preferably 30% to 40%.

[0012] [Formula 1]

number

[0013] In the above [Equation 1], λ1 is the long axis vector E of the crystal grain measured from image data obtained by scanning ion microscope analysis of the cross section of the positive electrode active material. I λ2 is the magnitude of the minor axis vector E of the crystal grain measured from image data obtained by analyzing the cross section of the positive electrode active material with a scanning ion microscope. II is the size of C D is the position unit vector P' and the major axis unit vector E of the grain I ' is the dot product value.

[0014] In the positive electrode active material according to the present invention, it is preferable that the ratio C1 of the crystal grains C among all the crystal grains in the outer region is larger than the ratio C2 of the crystal grains C among all the crystal grains in the inner region. Specifically, the difference between the ratio C1 of the crystal grains C among all the crystal grains in the outer region and the ratio C2 of the crystal grains C among all the crystal grains in the inner region may be 3% or more, 5% or more, 3% to 20%, or 3% to 15%.

[0015] Meanwhile, the positive electrode active material may further include crystal grains A having a degree of long axis orientation DoA of 0.5 to 1 and a degree of c-axis orientation of 0.5 to 1, crystal grains B having a degree of long axis orientation DoA of less than 0.5 and a degree of c-axis orientation of 0.5 to 1, and crystal grains D having a degree of long axis orientation DoA of less than 0.5 and a degree of c-axis orientation of less than 0.5.

[0016] In this case, it is preferable that in the outer region, a ratio C1 of crystal grains C in all crystal grains is greater than a ratio A1 of crystal grains A, a ratio B1 of crystal grains B, and a ratio D1 of crystal grains D.

[0017] In addition, the ratio of crystal grains A to all crystal grains in the cross section of the positive electrode active material particle may be 5% to 40%, preferably 10% to 30%, the ratio of crystal grains B may be 5% to 40%, preferably 10% to 30%, the ratio of crystal grains C may be 20% to 80%, preferably 25% to 60%, and the ratio of crystal grains D may be 5% to 40%, preferably 10% to 30%.

[0018] Meanwhile, the scanning ion microscope analysis may involve irradiating a cross section of the positive electrode active material with a focused ion beam to obtain a scanning ion microscope image, obtaining segmented data in units of crystal grains from the scanning ion microscope image using deep learning, and calculating the DoA represented by Equation 1 from the segmented data.

[0019] In addition, the Electron Backscatter Diffraction (EBSD) analysis may be performed by obtaining EBSD Euler map data including position information and Euler angle information of each crystal grain through EBSD measurement of a cross section of the positive electrode active material, and calculating a c-axis rotation vector Rc(x, y, z) of a crystal lattice of the crystal grain through the following [Equation 2]:

[0020] [Formula 2]

number

[0021] In the above [Equation 2], [X, Y, Z] is (0, 0, 1), and the Φ, θ, and Ψ are Euler angles obtained from Euler map data.

[0022] The positive electrode active material according to the present invention may be a lithium transition metal composite oxide represented by the following [Chemical Formula 1].

[0023] [Chemical formula 1] Li x [Ni a Co b M 1 c M 2 d ]O 2-y A y

[0024] In the above [Chemical Formula 1], Said M 1 is one or more elements selected from the group consisting of Mn and Al, 2is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and A is one or more elements selected from the group consisting of F, Cl, Br, I, At, and S, and 0.98≦x≦1.20, 0 <a<1、0<b<1、0<c<1、0≦d≦0.2、0≦y≦0.2である。

[0025] According to another embodiment, the present invention provides a positive electrode including the positive electrode active material according to the present invention, and a lithium secondary battery including the positive electrode. Effect of the Invention

[0026] The positive electrode active material of the present invention, when applied to a secondary battery, has excellent capacity characteristics and a small amount of gas generation, when the external region contains crystal grains with high long axis orientation and low c axis orientation at a specific ratio. Specifically, the movement of Li ions inside the crystal grains is in the direction of the ab plane of the crystal grains, but in the case of crystal grains with low c axis orientation, the contact between the ab plane, which is the lithium movement path inside the crystal grains, and the electrolyte is small, so that the amount of gas generation generated by the side reaction with the electrolyte can be reduced. Meanwhile, after Li ions are desorbed from the crystal grains, they move along the interface between the crystal grains. Therefore, when crystal grains with excellent long axis orientation, in which the long axis of the crystal grains is aligned from the particle center to the surface direction, are distributed in large numbers on the surface of the positive electrode active material, the lithium movement path is shortened, improving lithium mobility, and thus improving the capacity characteristics. Therefore, when the external region contains a high ratio of crystal grains with high long axis orientation and low c axis orientation, as in the present invention, it is possible to obtain an effect of improving both the capacity characteristics and the gas generation characteristics. [Brief description of the drawings]

[0027] [Figure 1] FIG. 2 is a scanning ion microscope image of a cross section of a positive electrode active material. [Diagram 2]It is a diagram showing the process of obtaining a segmentation image by analyzing a scanning ion microscope image of the cross-section of a positive electrode active material. [Diagram 3] It is a diagram showing the major axis orientation and DoA value of crystal grains. [Figure 4] It is a diagram showing an EBSD Euler map obtained by analyzing the cross-section of a positive electrode active material by Electron BackScatter Diffraction (EBSD). [Diagram 5] It is a diagram showing a c-axis orientation map of crystal grains.

Mode for Carrying Out the Invention

[0028] The terms and words used in this specification and the claims should not be construed as being limited to their ordinary or dictionary meanings. The inventor should interpret them as meanings and concepts consistent with the technical idea of the present invention in accordance with the principle that the inventor can appropriately define the concept of the terms in order to explain his invention in the best way.

[0029] In the present invention, "crystal grain" means a single crystal particle unit having a regular atomic arrangement. The size of the crystal grain can be measured by analyzing the X-ray diffraction data of the cross-section of the positive electrode active material by the Rietveld refinement method. For example, the size of the crystal grain can be obtained by performing X-ray diffraction analysis under the following conditions using an Empyreon XRD facility of Malyer Panalyticla to obtain XRD data, and then processing the XRD data using the Highscore program of Malyer panalytical. At this time, the full width at half maximum was set to be measured using the Caglioti equation.

[0030] <Conditions for X-ray diffraction analysis> Light source: Cu-target, 45 kV, 40 mA output, wavelength = 1.54 Å Detector: GaliPIX3D Sample preparation: Approximately 5 g of sample was filled into a 2 cm diameter holder and loaded onto the ratio stage. Measurement time: Approximately 30 minutes Measurement area: 2θ=15°~85°

[0031] In the present invention, the "primary particle" refers to the smallest particle unit that is distinguished as one mass when a cross section of a positive electrode active material is observed through a scanning electron microscope (SEM), and may consist of one crystal grain or multiple crystal grains. In the present invention, the average particle size of the primary particles may be measured by measuring each particle size distinguished in SEM data of a cross section of a positive electrode active material particle and then calculating the arithmetic average value of the particle sizes.

[0032] In the present invention, the term "secondary particles" refers to a secondary structure formed by the aggregation of a plurality of primary particles. The average particle size of the secondary particles can be measured using a particle size analyzer, and in the present invention, a Microtrac S3500 was used as the particle size analyzer.

[0033] Meanwhile, in the present invention, the ratio (%) of each crystal grain means (the number of the crystal grain / the total number of crystal grains present in the region)×100.

[0034] The present invention will be specifically described below.

[0035] The present inventors conducted repeated research to develop a positive electrode active material that can realize excellent life characteristics and resistance characteristics. As a result, they found that when the outer region of the positive electrode active material contains crystal grains with high long axis orientation and low c-axis orientation at a specific ratio, the capacity characteristics and gas generation characteristics of a secondary battery can be improved, and completed the present invention.

[0036] positive electrode active material As shown in FIG. 1, the cathode active material according to the present invention includes an inner region 20 that is a region from the center of the cathode active material particle to R / 2, where R is a distance from the center to the surface of the cathode active material particle, and an outer region 10 that is a region from R / 2 to the surface of the cathode active material particle. Among all the crystal grains in the outer region 10, the degree of long axis orientation DoA of the crystal grains represented by the following [Formula 1] is 0.5 to 1, and the ratio C1 of the crystal grains C having a degree of c-axis orientation of the crystal grains of less than 0.5 represented by the cross product value of the c-axis rotation vector Rc of the crystal lattice of the crystal grain and the position unit vector P' of the crystal grain obtained through an electron backscatter diffraction (EBSD) analysis is 25% to 80%, preferably 30% to 60%, more preferably 30% to 50%, and even more preferably 30% to 40%.

[0037] [Formula 1]

number

[0038] In the above [Formula 1], λ1 is the long axis vector E of the crystal grain measured from image data obtained by scanning ion microscope analysis of the cross section of the positive electrode active material. I λ2 is the magnitude of the minor axis vector E of the crystal grain measured from image data obtained by analyzing the cross section of the positive electrode active material with a scanning ion microscope. II is the size of C D is the position unit vector P' and the major axis unit vector E of the grain I ' is the dot product value.

[0039] First, the DoA expressed by the above [Equation 1] will be explained.

[0040] The DoA value represented by the above formula (1) indicates the orientation of the long axis of crystal grains, and can be determined using data obtained through scanning ion microscope analysis.

[0041] Specifically, a cross section of the positive electrode active material is irradiated with a focused ion beam to obtain a scanning ion microscope image, and then segmented data is obtained from the scanning ion microscope image in units of crystal grains using deep learning. The degree of long axis orientation (DoA) of the crystal grains, expressed by the formula (1), can be calculated from the segmented data.

[0042] The method for determining the DoA value through scanning ion microscope analysis will be described in more detail below.

[0043] A scanning ion microscope is a device that irradiates an ion beam onto the surface of a sample and measures the surface structure of the sample through the resulting signal ion image. Since the reflectance of the ion beam changes on different crystal planes, a scanning ion microscope can be used to obtain a cross-sectional image of the positive electrode active material particles, which are separated into single crystal grains having the same atomic arrangement structure. Figure 1 shows a scanning ion microscope image of the cross-section of a positive electrode active material particle. It can be seen from Figure 1 that the cross-sectional image of the positive electrode active material particles is separated into crystal grains.

[0044] Next, the scanning ion microscope image obtained as described above is analyzed to obtain data segmented in units of grains, and the image analysis may be performed using deep learning.

[0045] A process of obtaining segmented data information by analyzing a scanning ion microscope image is shown in Fig. 2. As shown in Fig. 2, the image analysis may be performed by, for example, detecting a boundary line from a scanning ion microscope image through deep learning, and then obtaining image data segmented in units of grains using the boundary line.

[0046] In this case, the boundary detection may be performed using an AutoEncoder Neural Network (U-NET) algorithm, and the segmentation may be performed using a Watershed segmentation algorithm, etc.

[0047] Since a scanning ion microscope image itself does not contain digitized information, in the present invention, segmented data information for each crystal grain is obtained through deep learning, and information such as the shape and position of the crystal grains can be digitized.

[0048] Once segmented data is obtained through scanning ion microscope image analysis as described above, the position vector, major axis vector, and minor axis vector of the grain to be measured can be obtained from the data, and the DoA value of Equation 1 can be calculated using the vectors.

[0049] [Formula 1]

number

[0050] In the above [Formula 1], λ1 is the long axis vector E of the crystal grain measured from image data obtained by scanning ion microscope analysis of the cross section of the positive electrode active material. I At this time, the magnitude of the major axis vector E I means a vector that passes through the center of gravity of the crystal grain and has the smallest sum of the distance between the vector and each pixel in the crystal grain.

[0051] λ2 is the minor axis vector E of the crystal grain measured from the image data obtained by analyzing the cross section of the positive electrode active material with a scanning ion microscope. II At this time, the magnitude of the short axis vector E II means the vector that passes through the center of gravity of the crystal grain and has the largest sum of the distance between the vector and each pixel in the crystal grain.

[0052] On the other hand, the above C D is the position unit vector P' of the grain and the major axis unit vector E I The position unit vector P′ of the crystal grain is a vector obtained by converting a position vector connecting the center of the cross section of the positive electrode active material particle to the center of gravity of the crystal grain so that the magnitude of the vector is 1, and the major axis unit vector E I ' is the major axis vector E I is a vector converted so that its magnitude becomes 1.

[0053] The DoA value calculated using the formula 1 indicates the degree to which the long axis of the crystal grain is inclined with respect to the shortest line segment that passes through the crystal grain and connects the center and surface of the positive electrode active material, and the closer the DoA value is to 1, the smaller the angle between the long axis of the crystal grain and the shortest line segment, and the closer the DoA value is to 0, the larger the angle between the long axis of the crystal grain and the shortest line segment. In other words, the closer the DoA is to 1, the higher the long axis orientation of the crystal grain.

[0054] The DoA values ​​obtained by the above method and the long axis of the corresponding crystal grains are shown in Figure 3. As shown in Figure 3, in the case of crystal grain 1, in which the angle between the shortest line segment connecting the center and surface of the positive electrode active material particle and the long axis of the crystal grain is small, the DoA appears to be 0.965, which is close to 1, while in the case of crystal grain 2, in which the angle between the shortest line segment connecting the center and surface of the positive electrode active material particle and the long axis of the crystal grain is large, the DoA appears to be small at 0.352.

[0055] Meanwhile, the ratio of crystal grains having a specific longitudinal orientation value in the outer region and the inner region of the positive active material particle can be measured by mapping the longitudinal orientation information of each crystal grain.

[0056] Next, the degree of c-axis orientation of crystal grains will be described.

[0057] The degree of c-axis orientation of the crystal grain indicates the orientation of the c-axis of the crystal lattice of the crystal grain, and is the cross product of the c-axis rotation vector Rc of the crystal lattice of the crystal grain obtained through Electron Backscatter Diffraction (EBSD) analysis and the position unit vector P' of the crystal grain.

[0058] Specifically, the degree of c-axis orientation of the crystal grains can be obtained by obtaining EBSD Euler map data including position information and Euler angle information of each crystal grain through Electron Backscatter Diffraction (EBSD) measurement of a cross section of the positive electrode active material, determining a c-axis rotation vector Rc of the crystal lattice using the EBSD Euler map data, and calculating the cross product of the c-axis rotation vector Rc of the crystal lattice and the position unit vector P' of the crystal grain.

[0059] The method for determining the degree of c-axis orientation of crystal grains according to the present invention will now be described in detail.

[0060] Electron backscatter diffraction analysis is a method of measuring the crystallographic phase and crystallographic orientation of a sample using the diffraction pattern, and analyzing the crystallographic information of the sample based on the results. When a sample (i.e., a cross-section of a positive active material) is tilted at a large angle to the direction of incidence of the electron beam in a scanning electron microscope, the incident electron beam is scattered within the sample, and a diffraction pattern appears in the direction of the surface of the sample, which is called an electron backscatter diffraction pattern (EBSP). Since the electron backscatter diffraction pattern responds to the crystal orientation of the area irradiated with the electron beam, it can be used to accurately measure the crystal orientation of the sample, and Euler map data containing various information related to the crystal orientation of the entire sample can be obtained through EBSD software. Figure 4 shows an Euler map obtained by analyzing the cross-section of a positive active material particle using electron backscatter diffraction (EBSD).

[0061] The EBSD Euler map data includes position vector information and Euler angle information of each crystal grain. Meanwhile, by using the Euler angle information, the c-axis rotation vector Rc of the crystal lattice in each crystal grain can be obtained.

[0062] The c-axis rotation vector Rc of the crystal lattice indicates the direction in which the c-axis of the crystal grain rotates with respect to the shortest line segment that passes through the crystal grain and connects the center and surface of the positive electrode active material.

[0063] Specifically, the c-axis rotation vector Rc of the crystal lattice can be expressed as (x, y, z) calculated by the following [Equation 2].

[0064] [Formula 2]

number

[0065] In the above [Equation 2], [X, Y, Z] is (0, 0, 1), and the Φ, θ, and Ψ are the Euler angles of each grain obtained from the Euler map data.

[0066] The degree of c-axis orientation of the crystal grains can be calculated using the c-axis rotation vector Rc of the crystal lattice calculated as described above and the position vector information of each crystal grain included in the Euler map data. Specifically, the degree of c-axis orientation of the crystal grains can be quantified by the cross product of the c-axis rotation vector Rc of the crystal lattice and the position unit vector P' of the crystal grain.

[0067] In this case, the position unit vector P' means the position vector of the crystal grain converted so that its magnitude is 1. For example, if the position vector of the crystal grain is (a, b, o), the position unit vector is

[0068]

number

[0069] It becomes.

[0070] The cross product of the position unit vector P' and the c-axis rotation vector Rc of the crystal lattice is a numerical value indicating the degree of c-axis orientation of the crystal grain in the positive electrode active material particle. Specifically, when the cross product of the position unit vector P' and the c-axis rotation vector Rc of the crystal lattice is 1, it means that the c-axis of the crystal grain is aligned perpendicular to the shortest line segment connecting the center and the surface of the positive electrode active material particle, and when the cross product is 0, it means that the c-axis of the crystal grain is aligned horizontally to the shortest line segment.

[0071] In the positive electrode active material, the mobility of lithium ions when moving along a direction perpendicular to the c-axis is 10 times faster than when moving along the c-axis. Therefore, a lithium path is formed along a direction perpendicular to the c-axis. In addition, when the lithium path is formed parallel to the shortest line segment connecting the center and surface of the positive electrode active material particle, the lithium migration distance is minimized, improving the lithium conductivity. Therefore, the closer the cross product of the position unit vector P' and the c-axis rotation vector Rc of the crystal lattice is to 1, the better the orientation of the crystal grains can be determined.

[0072] Meanwhile, by combining the c-axis orientation degrees of each crystal grain obtained as described above, the c-axis orientation degree of the entire crystal grain in the cross section of the positive electrode active material particle can be obtained. Figure 5 shows a c-axis orientation map of the crystal grains of the positive electrode active material obtained by combining the c-axis orientation degrees of each crystal grain. In Figure 5, the redder the color, the better the c-axis orientation, and the bluer the color, the worse the c-axis orientation. Using the c-axis orientation map as described above, the ratio of crystal grains that satisfy the c-axis orientation conditions in the outer and inner regions of the positive electrode active material particle can be obtained.

[0073] According to the research of the present inventors, when the ratio (hereinafter referred to as C1) of the crystal grains (hereinafter referred to as crystal grains C) having the degree of major axis orientation DoA of the crystal grains represented by [Formula 1] among all the crystal grains in the outer region of the positive electrode active material particles is 25% to 80%, preferably 30% to 60%, excellent capacity characteristics and gas generation characteristics are shown. When the ratio of the crystal grains C in the outer region exceeds 25% or 80%, the improvement effect of the capacity characteristics and gas generation characteristics is insignificant.

[0074] In addition, in the positive electrode active material of the present invention, the ratio C1 of the crystal grains C in the outer region is preferably larger than the ratio C2 of the crystal grains C in the inner region. When the ratio of the crystal grains C in the outer region is larger, the gas generation suppression effect is more excellent.

[0075] Specifically, the difference between the ratio C1 of the crystal grains C in all the crystal grains in the outer region and the ratio C2 of the crystal grains C in all the crystal grains in the inner region is preferably 3% or more, 5% or more, 3% to 20%, or 3% to 15%. When the difference in the ratio of the crystal grains C between the outer region and the inner region satisfies the above range, the capacity improvement effect and the gas generation reduction effect are excellent, and when the difference in the ratio of the crystal grains C between the outer region and the inner region is high, the effect is further improved.

[0076] Meanwhile, the positive electrode active material according to the present invention may further include, in addition to the crystal grains C, crystal grains having a c-axis orientation degree of 0.5 to 1 and a long axis orientation degree DoA of 0.5 to 1 (hereinafter referred to as crystal grains A), crystal grains having a c-axis orientation degree of 0.5 to 1 and a long axis orientation degree DoA of less than 0.5 (hereinafter referred to as crystal grains B), and crystal grains having a c-axis orientation degree of less than 0.5 and a long axis orientation degree DoA of less than 0.5 (hereinafter referred to as crystal grains D) in the external region and the internal region.

[0077] Meanwhile, in the positive electrode active material of the present invention, it is preferable that the ratio C1 of crystal grains C in the total crystal grains of the outer region is larger than the ratios of other crystal grains, i.e., the ratio A1 of crystal grains A, the ratio B1 of crystal grains B, and the ratio D1 of crystal grains D. That is, it is preferable that C1>B1, C1>A1, and C1>D1 are satisfied.

[0078] During charging and discharging, the greater the contact area between the lithium ion migration path (Li path) and the electrolyte, the more gas is generated and the faster the structural degradation occurs. In the case of crystal grain C, which has a low degree of c-axis orientation, the contact area between the electrolyte and the ab plane, which is the lithium migration path inside the crystal grain, is small, so the amount of gas generated is small. In contrast, in the case of crystal grain A and crystal grain B, the degree of c-axis orientation is high, so the contact area between the electrolyte and the ab plane is large, and therefore, when crystal grain A or crystal grain B is present at a high ratio in the external region, the amount of gas generated increases.

[0079] On the other hand, in the case of crystal grain D, the amount of gas generation is small, but the degree of c-axis orientation and the degree of long axis orientation are both low, making it difficult for lithium ions to be inserted and removed, resulting in a significant decrease in capacity characteristics.In contrast, in the case of crystal grain C, the degree of long axis orientation is high, so the migration distance of lithium ions along the interface between crystal grains during charging and discharging is short, resulting in excellent capacity characteristics.

[0080] Therefore, when the ratio C1 of the crystal grains C among all the crystal grains in the outer region is higher than the ratio of the other crystal grains, both the gas generation characteristic and the capacity characteristic can be excellently realized.

[0081] Meanwhile, in the positive electrode active material according to the present invention, among the crystal grains in the entire cross section of the positive electrode active material particle, the ratio of crystal grains A may be 5% to 40%, preferably 10% to 30%, the ratio of crystal grains B may be 5% to 40%, preferably 10% to 30%, the ratio of crystal grains C may be 20% to 80%, preferably 25% to 60%, and the ratio of crystal grains D may be 5% to 40%, preferably 10% to 30%. When the ratio of crystal grains in the entire positive electrode active material satisfies the above ranges, the gas generation suppression effect and the capacity improvement effect are more excellent.

[0082] Meanwhile, the crystal grain ratio of the positive electrode active material varies depending on the composition of the precursor used in producing the positive electrode active material, the shape and orientation of the crystal grains of the precursor, the type of doping element, and / or the firing temperature, etc., and therefore, by appropriately adjusting the type of precursor, the doping element, the firing temperature, etc., a positive electrode active material satisfying the crystal grain ratio of the present invention can be produced.

[0083] Meanwhile, the positive electrode active material according to the present invention may be a lithium composite transition metal oxide containing two or more transition metals, for example, a lithium composite transition metal oxide represented by the following [Chemical Formula 1].

[0084] [Chemical formula 1] Li x [Ni a Co b M 1 c M 2 d ]O2-y A y

[0085] In the above [Chemical Formula 1], the M 1 may be one or more elements selected from the group consisting of Mn and Al.

[0086] The M 2 may be one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

[0087] Also, the A may be one or more elements selected from the group consisting of F, Cl, Br, I, At, and S.

[0088] The x represents the molar ratio of Li to the total number of moles of transition metals, and 0.98 ≤ x ≤ 1.20, preferably 0.99 ≤ x ≤ 1.10, more preferably 1.0 ≤ x ≤ 1.10.

[0089] The a represents the molar ratio of Ni to the total number of moles of transition metals, and 0 < a < 1, preferably 0.3 ≤ a < 1, more preferably 0.6 ≤ a < 1, still more preferably 0.8 ≤ a < 1, even more preferably 0.85 ≤ a < 1.

[0090] The b represents the molar ratio of Co to the total number of moles of transition metals, and 0 < b < 1, preferably 0 < b < 0.7, more preferably 0 < b < 0.4, still more preferably 0 < b < 0.2, even more preferably 0 < b ≤ 0.1.

[0091] The c represents the molar ratio of M 1 to the total number of moles of transition metals, and 0 < c < 1, preferably 0 < c < 0.7, more preferably 0 < c < 0.4, still more preferably 0 < c < 0.2, even more preferably 0 < c ≤ 0.1.

[0092] The d represents the molar ratio of M2 and may be 0≦d≦0.2, preferably 0≦d≦0.15, and more preferably 0≦d≦0.10.

[0093] The y indicates the molar ratio of the A element substituted at the oxygen position, and may be 0≦y≦0.2, preferably 0≦y≦0.15, and more preferably 0≦y≦0.10.

[0094] Meanwhile, the positive electrode active material may have a crystal grain size of 100 nm to 200 nm, preferably 100 nm to 180 nm, and more preferably 100 nm to 150 nm. If the crystal grain size is too large, a rock salt phase may be formed, which may reduce the resistance characteristics and life characteristics, and if the crystal grain size is too small, the contact area with the electrolyte may increase, which may cause early degradation.

[0095] In addition, the positive electrode active material may have an average primary particle size of 0.05 μm to 4 μm, preferably 0.1 μm to 2 μm. If the average primary particle size is too large, a rock salt phase may be formed, which may reduce resistance characteristics and life characteristics, and if the average primary particle size is too small, the contact area with the electrolyte may increase, which may cause early degradation.

[0096] In addition, the positive electrode active material may have an average secondary particle size of 2 μm to 25 μm, preferably 4 μm to 18 μm. When the average secondary particle size satisfies this range, it is possible to prevent the positive electrode active material particles from cracking during the rolling process and to prevent the processability from deteriorating during the preparation of the slurry.

[0097] positive electrode Next, the positive electrode according to the present invention will be described.

[0098] The positive electrode includes a positive electrode active material according to the present invention. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material according to the present invention.

[0099] Here, since the positive electrode active material is the same as that described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0100] The positive electrode current collector may contain a metal with high electrical conductivity, and is not particularly limited as long as the positive electrode active material layer is easily attached and is non-reactive in the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. The positive electrode current collector may have a thickness of typically 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0101] The positive electrode active material layer may selectively contain a conductive material, a binder, and the like, as necessary, in addition to the positive electrode active material.

[0102] At this time, the positive electrode active material may be included in an amount of 80 to 99 wt %, more specifically, 85 to 98.5 wt %, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics may be exhibited when included in the above content range.

[0103] The conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it does not cause chemical changes in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and other carbon-based materials; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive tubes such as carbon nanotubes; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like. One or a mixture of two or more of these can be used. The conductive material can be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0104] The binder serves to improve adhesion between particles of the positive electrode active material and adhesion between the positive electrode active material and the current collector.Specific examples of the binder include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylalcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluorine rubber, polyacrylic acid, polymers in which hydrogen is substituted with Li, Na, or Ca, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 0.1 to 15 wt % based on the total weight of the positive electrode active material layer.

[0105] The positive electrode may be manufactured by a conventional method for manufacturing a positive electrode, except for using the positive electrode active material described above. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder, a conductive material, and a dispersant in a solvent to prepare a positive electrode slurry composition, which is coated on a positive electrode current collector, followed by drying and rolling.

[0106] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethyl formamide (DMF), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, binder, and dispersant in consideration of the thickness of the applied slurry and the manufacturing yield, and to have a viscosity that can show excellent thickness uniformity when applied to manufacture a positive electrode.

[0107] Alternatively, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0108] secondary battery The present invention also provides an electrochemical device including the positive electrode, which may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0109] The lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. The positive electrode is the same as that described above, so a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0110] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly including the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0111] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0112] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may be formed with fine irregularities on the surface of the current collector to enhance the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, it may be used in various forms, such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0113] The negative electrode active material layer includes a negative electrode active material and, optionally, a binder and a conductive material.

[0114] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. Also, a metallic lithium thin film may be used as the negative electrode active material. Also, both low crystalline carbon and high crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0115] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0116] The binder is a component that helps the conductive material, active material, and current collector to bond with each other, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0117] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10 wt % or less, preferably 5 wt % or less, based on the total weight of the negative electrode active material layer. The conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0118] For example, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the resulting film from the support and laminating the film on the negative electrode current collector.

[0119] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular restrictions. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte humidification capacity is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, a separator coated with a ceramic component or a polymer material to ensure heat resistance or mechanical strength may be used, and may be selectively used in a single layer or multilayer structure.

[0120] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, and the like that can be used in the production of lithium secondary batteries, but are not limited to these.

[0121] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0122] The organic solvent may be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; an ether solvent such as dibutyl ether or tetrahydrofuran, etc.; a ketone solvent such as cyclohexanone, etc.; an aromatic hydrocarbon solvent such as benzene or fluorobenzene, etc.; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), propylene carbonate (propylene carbonate), etc. Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a hydrocarbon group having a linear, branched or cyclic structure with 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ion conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) is more preferred.

[0123] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the anion of the lithium salt may be F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - The lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt may be used at a concentration in the range of 0.1 to 2.0M. If the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0124] As described above, the lithium secondary battery including the positive electrode active material according to the present invention exhibits excellent capacity and life characteristics, and can be usefully used in various fields such as portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles.

[0125] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention may be modified in various forms, and the scope of the present invention should not be construed as being limited to the examples detailed below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. EXAMPLES

[0126] Production Example 1 - Production of Positive Electrode Active Material Precursor A NiSO4, CoSO4, and MnSO4 were mixed in distilled water in amounts such that the molar ratio of nickel:cobalt:manganese was 92:4:4 to prepare a 2.4 M transition metal aqueous solution.

[0127] Next, deionized water was added to the reactor, and nitrogen gas was purged into the reactor to remove dissolved oxygen in the water and adjust the reactor to a non-oxidizing atmosphere. Then, 7.96 M NaOH was added to maintain the pH of the reactor at 11.9.

[0128] Then, the transition metal aqueous solution was added to the reactor at a rate of 850 mL / hr, and the NaOH aqueous solution was added at a rate of 510 mL / hr and the NH4OH aqueous solution was added at a rate of 160 mL / hr. The coprecipitation reaction was carried out for 40 hours under the conditions of a reaction temperature of 50° C., pH 11.4, and a stirring speed of 600 rpm to obtain an average particle size D 50 is 15μm, Ni 0.92 Co 0.04 Mn 0.04 A positive electrode active material precursor A represented by (OH)2 was prepared.

[0129] Production Example 2 - Production of Positive Electrode Active Material Precursor B The average particle size D was measured in the same manner as in Preparation Example 1, except that the coprecipitation reaction was carried out for 12 hours. 50 is 4μm, Ni 0.92 Co 0.04 Mn 0.04 A positive electrode active material precursor B represented by (OH)2 was prepared.

[0130] Example 1 The positive electrode active material precursor A prepared in Preparation Example 1 was mixed with LiOH so that the molar ratio of Li:transition metals (Ni+Co+Mn) was 1.05:1, and Nb2O3 was added thereto so that the molar ratio of transition metals (Ni+Co+Mn):Nb was 99.75:0.25, and the mixture was fired at 770° C. for 13 hours to obtain Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Nb 0.0025 Manufactured the O2.

[0131] Next, the Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Nb 0.0025 The O2 was washed with water, dried, and then mixed with 500 ppm of boric acid and heat-treated at 300°C to produce a B-coated positive electrode active material.

[0132] Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that the calcination was performed at 790°C.

[0133] Example 3 The positive electrode active material precursor A prepared in Preparation Example 1 was mixed with LiOH in a molar ratio of Li:transition metals (Ni+Co+Mn) of 1.05:1, and MgO was added thereto in a molar ratio of transition metals (Ni+Co+Mn):Mg of 99.75:0.25. The mixture was then fired at 770° C. for 13 hours to obtain Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Mg 0.0025 Manufactured the O2.

[0134] Next, the Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Mg 0.0025 The O2 was washed with water, dried, and then mixed with 500 ppm of boric acid and heat-treated at 300°C to produce a B-coated positive electrode active material.

[0135] Comparative Example 1 The positive electrode active material precursor A prepared in Preparation Example 1 and LiOH were mixed so that the molar ratio of Li:transition metal (Ni+Co+Mn) was 1.05:1, and the mixture was fired at 780° C. for 13 hours to obtain Li[Ni 0.92 Co 0.04 Mn 0.04 ]O2 was produced.

[0136] Next, the Li[Ni 0.92 Co 0.04 Mn 0.04 ]O2 was washed with water, dried, and then mixed with 500 ppm of boric acid and heat-treated at 300°C to prepare a B-coated positive electrode active material.

[0137] Comparative Example 2 The positive electrode active material precursor B prepared in Preparation Example 2 was mixed with LiOH so that the molar ratio of Li:transition metals (Ni+Co+Mn) was 1.07:1, and Nb2O3 was added thereto so that the molar ratio of transition metals (Ni+Co+Mn):Nb was 99.75:0.25, and the mixture was fired at 770° C. for 13 hours to obtain Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Nb 0.0025 Manufactured the O2.

[0138] Next, the Li[Ni 0.92 Co 0.04 Mn 0.04 ] 0.9975 Nb 0.0025 The O2 was washed with water, dried, and then mixed with 500 ppm of boric acid and heat-treated at 300°C to produce a B-coated positive electrode active material.

[0139] Experimental Example 1 Using an ion milling system (Hitachi, IM4000), the positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were cross-sectioned, and then the above-mentioned scanning ion microscope analysis and electron backscatter diffraction (EBSD) analysis were performed to measure the ratios of crystal grains A, B, C, and D in the outer and inner regions.

[0140] The measurement results are shown in Table 1 below.

[0141] [Table 1]

[0142] Experimental Example 2: Evaluation of battery characteristics The positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2, conductive material (denka black), and binder (PVDF) were mixed in a weight ratio of 97.5:1:1.5 in N-methyl-2-pyrrolidone (NMP) solvent to prepare positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried, and rolled to prepare a positive electrode.

[0143] A lithium metal electrode was used as the negative electrode.

[0144] The electrode assembly was prepared by interposing a separator between the positive and negative electrodes, and then placed inside a battery case, and an electrolyte was injected to prepare a lithium secondary battery. The electrolyte was prepared by dissolving 1M LiPF6 in an organic solvent in which ethylene carbonate: ethyl methyl carbonate: diethyl carbonate was mixed in a volume ratio of 3:3:4.

[0145] Next, the secondary batteries were charged at a constant current of 0.1 C at 25° C. up to 4.2 V. Thereafter, they were discharged at a constant current of 0.1 C up to 3 V, and the initial charge capacity and the initial discharge capacity were measured.

[0146] The measurement results are shown in Table 2 below.

[0147] In addition, the positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2, conductive material (denka black), and binder (PVDF) were mixed in a weight ratio of 97.5:1.0:1.5 in N-methyl-2-pyrrolidone (NMP) solvent to prepare positive electrode slurries. The positive electrode slurries were applied to one side of an aluminum current collector, dried, and rolled to prepare positive electrodes.

[0148] Next, the negative electrode active material (natural graphite), the conductive material (carbon black), and the binder (PVDF) were mixed in a weight ratio of 95.6:1.0:3.4 in N-methylpyrrolidone solvent to prepare a negative electrode slurry. The negative electrode slurry composition was applied to a copper current collector, dried, and then rolled to prepare a negative electrode.

[0149] The electrode assembly was prepared by interposing a separator between the positive and negative electrodes, and then placed inside a battery case, and an electrolyte was injected to prepare a lithium secondary battery. The electrolyte was prepared by dissolving 0.7M LiPF6 in an organic solvent in which ethylene carbonate: ethyl methyl carbonate was mixed in a volume ratio of 3:7.

[0150] Each of the lithium secondary batteries was charged at a constant current of 0.1 C at 25° C. up to 4.2 V. Then, discharge was performed at a constant current of 0.1 C down to 3 V (1 cycle), and then 200 cycles of charge and discharge were performed at 45° C. and 0.33 C in the range of 3 V to 4.2 V.

[0151] The lithium secondary battery charged and discharged for one cycle and the lithium secondary battery charged and discharged for 200 cycles were each perforated in a vacuum chamber to discharge the gas inside the battery and collect it inside the vacuum chamber, and the gas in the chamber was quantitatively analyzed for the amount of gas generated using a gas chromatography-flame ionization detector (GC-FID).The amount of gas generated in the lithium secondary battery charged and discharged for 200 cycles was then divided by the amount of gas generated in the lithium secondary battery charged and discharged for one cycle, and multiplied by 100 to calculate the gas increase (%).

[0152] [Table 2]

[0153] As shown in Table 2, the secondary batteries using the positive electrode active materials of Examples 1 to 3, in which the ratio of crystal grains C in the outer region of the positive electrode active material particles satisfies the range of the present invention, had better capacity characteristics and less gas generation than the secondary batteries using the positive electrode active materials of Comparative Examples 1 and 2. Furthermore, when using the positive electrode active materials of Examples 1 and 3, in which the difference in the ratio of crystal grains C between the outer region and the inner region is large, at 5% or more, such an improvement effect was even more outstanding.

Claims

1. When the distance from the center to the surface of the positive electrode active material particle is R, the positive electrode active material particle includes an inner region that is a region from the center to R / 2, and an outer region that is a region from R / 2 to the surface of the positive electrode active material particle, Among all the crystal grains in the outer region, the degree of orientation of the long axis of the crystal grains, represented by the following [Formula 1], is 0.5 to 1, and the ratio (C1) of the crystal grains C having a degree of orientation of the c-axis of the crystal grains, represented by the cross product value of the c-axis rotation vector Rc of the crystal lattice of the crystal grains and the position unit vector P' of the crystal grains obtained through an electron backscatter diffraction (EBSD) analysis, is less than 0.5, is 25% to 80%; The EBSD analysis is carried out by measuring a cross section of the positive electrode active material using electron backscatter diffraction (EBSD) to obtain EBSD Euler map data including position information and Euler angle information of each crystal grain, and calculating a c-axis rotation vector Rc(x, y, z) of the crystal lattice of the crystal grain according to the following Equation 2: The position unit vector P′ of the crystal grain is a vector obtained by converting a position vector connecting the center of the cross section of the positive electrode active material particle to the center of gravity of the crystal grain so that the magnitude of the vector is 1, The positive electrode active material particles are spherical, The positive electrode active material is a lithium composite transition metal oxide represented by the following [Chemical Formula 1]: [Formula 1] [0010] In the formula 1, λ 1 is the long axis vector E of the crystal grain measured from image data obtained by analyzing the cross section of the positive electrode active material with a scanning ion microscope. I is the size of λ 2 is the minor axis vector E of the crystal grain measured from image data obtained by analyzing the cross section of the positive electrode active material with a scanning ion microscope. II is the size of Said C D is the position unit vector P' and the major axis unit vector E of the grain I ' is the dot product value of [Formula 2] [0025] In the formula 2, [X, Y, Z] is (0, 0, 1), and Φ, θ, and Ψ are Euler angles obtained from Euler map data. [Chemical formula 1] Li x [Nia Co b M 1 c M 2 d ] O 2-y A y In the above [Chemical Formula 1], M 1 is one or more elements selected from the group consisting of Mn and Al; M2 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; A is one or more elements selected from the group consisting of F, Cl, Br, I, At, and S; 0.98≦x≦1.20, 0<a<1, 0<b<1, 0<c<1, 0≦d≦0.2, and 0≦y≦0.

2.

2. The positive electrode active material according to claim 1, wherein a ratio (C1) of the crystal grains C to the total crystal grains in the outer region is 30% to 60%.

3. 3. The positive electrode active material according to claim 1, wherein a ratio (C1) of the crystal grains C in all crystal grains in the outer region is greater than a ratio (C2) of the crystal grains C in all crystal grains in the inner region.

4. The positive electrode active material according to claim 3 , wherein a difference between a ratio (C1) of the crystal grains C in all crystal grains in the outer region and a ratio (C2) of the crystal grains C in all crystal grains in the inner region is 3% or more.

5. The positive electrode active material is A crystal grain A having a degree of long axis orientation DoA of 0.5 to 1 and a degree of c-axis orientation of the crystal grains of 0.5 to 1; Crystal grains B, in which the degree of long axis orientation DoA of the crystal grains is less than 0.5 and the degree of c-axis orientation of the crystal grains is 0.5 to 1; and The positive electrode active material according to claim 1 , further comprising crystal grains D having a degree of long axis orientation DoA of the crystal grains of less than 0.5 and a degree of c-axis orientation of the crystal grains of less than 0.

5.

6. 6. The positive electrode active material according to claim 5, wherein the ratio (C1) of crystal grains C in the total crystal grains of the outer region is greater than the ratio (A1) of crystal grains A, the ratio (B1) of crystal grains B, and the ratio (D1) of crystal grains D.

7. The cathode active material according to claim 5 or 6, wherein the ratio of crystal grains A to the total crystal grains in the cross section of the cathode active material particle is 5% to 40%, the ratio of crystal grains B is 5% to 40%, the ratio of crystal grains C is 20% to 80%, and the ratio of crystal grains D is 5% to 40%.

8. 8. The cathode active material according to claim 1, wherein the scanning ion microscope analysis includes irradiating a cross section of the cathode active material with a focused ion beam to obtain a scanning ion microscope image, and then using deep learning to obtain segmentation data in units of crystal grains from the scanning ion microscope image, and calculating the DoA represented by [Equation 1] from the segmented data.

9. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 8.

10. A lithium secondary battery comprising the positive electrode according to claim 9.

Citation Information

Patent Citations

  • Lithium secondary cell positive electrode activator, and manufacturing method of the same

    JP2002158011A

  • Positive electrode composition for nonaqueous electrolyte secondary batteries and method for manufacturing the same

    JP2015111560A

  • Positive electrode active material for secondary battery and secondary battery including the same

    JP2018521456A

  • Cathode active material for lithium secondary battery, method for manufacturing the same and lithium secondary battery having positive electrode including cathode active material

    JP2019200991A

  • Positive active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same

    JP2020087925A